Baclofen but Not Diazepam Alleviates Alcohol-Seeking Behavior and Hypothalamic–Pituitary–Adrenal Axis Dysfunction in Stressed Withdrawn Mice - Rabat, Yolaine; Henkous, Nadia; Corio, Marc; Nogues, Xavier; Beracochea, Daniel (Frontiers in Psychiatry, 2019)
This study compares the impact of repeated injections of baclofen (an agonist of GABAB receptors) or diazepam (a benzodiazepine having an agonist action on GABAA receptors) given during the alcohol-withdrawal period on the stress-induced restoration of alcohol-seeking behavior and hypothalamic–pituitary–adrenal (HPA) axis dysfunction after a long (4 weeks) abstinence. Thus, C57BL/6 mice were submitted to a 6-month alcohol consumption [12% volume/volume (v/v)] and were progressively withdrawn to water before testing. Diazepam (Valium®, Roche) and baclofen (Baclofen®, Mylan) were administered intraperitoneally for 15 consecutive days (1 injection/day) during the withdrawal period at decreasing doses ranging from 1.0 mg/kg (Day 15) to 0.25 mg/kg (Day 1) for diazepam and from 1.5 mg/kg (Day 15) to 0.37 mg/kg (Day 1) for baclofen. Alcohol-seeking behavior was evaluated by alcohol-place preference in an odor recognition task. In the stress condition, mice received three electric footshocks 45 min before behavioral testing. Blood was sampled immediately after behavioral testing, and plasma corticosterone concentrations were measured by commercial enzyme immunoassay kits. Results showed that non-stressed withdrawn mice did not exhibit alcohol-place preference or alteration of plasma corticosterone concentrations relative to water controls. After stress, however, withdrawn mice exhibited a significant alcohol-place preference and higher circulating corticosterone concentrations as compared to stressed water controls. Interestingly, repeated administration during the withdrawal phase of baclofen but not diazepam suppressed both the alcohol-place preference and normalized corticosterone levels in stressed withdrawn animals. In conclusion, this study evidences that a pre-treatment with baclofen but not with diazepam during the withdrawal phase normalized, even after a long period of abstinence, the HPA axis response to stress, which contributes to the long-term preventing effects of this compound on alcohol-seeking behavior.